12-hydroxycorniculatolide A from the mangrove tree, Lumnitzera littorea - Puttandon Wongsomboon (2018)
© Copyright 2018 Natural Product Communciations Inc. All Rights Reserved. A new macrocyclic lactone, 12-hydroxycorniculatolide A (1), along with three known compounds, corniculatolide A (2), 12-hydroxy-11-O-methylcorniculatolide A (3) and 6,7-dimethoxycoumarin (4) were isolated from the methanolic extract of the twigs of Lumnitzera littorea. All compounds were characterized using spectroscopic methods. All compounds were screened against a panel of six Gram positive and five Gram negative bacteria.